Transmisi infeksi Helicobacter Pylori di antara anggota keluarga - Susanna Hilda Hutajulu, Budi Yuli Setianto dan Siti Nurjanah (Berita Kedokteran Masyarakat (BKM), 2004)
Background: The transmission of Helicobacter pylon (H. pylon) infection between family members plays important role in the spreading of infection. Many factors have been known to affect the transmission. Objective: This study aimed at determining whether an existence of infected chronic dyspepsia patient in the family will increase infection prevalence of the other family members, and assessing risk factors well known to increase infection transmission in the family. Methods: This study was cross sectional and was conducted in Yogyakarta. Anti-H. pylon serology was performed to determine the infection status of family members of infected chronic dyspepsia patients compared to family members of uninfected ones. A questionnaire was used to assess the risk factors. Results: There were 118 subjects who met the eligibility criteria. The infection prevalence among all subjects was 38,1%. There were 16 families (76,19%) from infected patients and 13 families (61,90%) from uninfected ones proven seropositivity among the members. The prevalence ratio was 1,23 and the difference was not statistically significant (p= 0,317, 95% Confidence Interval 0,82-1,86). Univariate analysis for the variables suspected to increase seropositivity prevalence in the family was not statistically significant. Conclusion: The infection prevalence of H. pylon was higher among family members of infected chronic dyspepsia patients than among family members of uninfected ones, but it was not statistically different. All of well known risk factors did not seem to affect the prevalence rate. Keywords: Helicobacter pylori, transmission, family members, seropositivity